The Old Indies at the French Court: Johan Maurits’s Gift to Louis XIV - Carrie Anderson (Early Modern Low Countries)
In 1679 Prince Johan Maurits (1604-1679), the former governor-general of Dutch Brazil, presented French King Louis XIV (r. 1643-1715) with an extravagant gift comprised of Brazilian-themed images and objects, including a set of eight cartoons by the Dutch artist Albert Eckhout (1610-1665), which would be transformed into a set of tapestries known as the Old Indies (Anciennes Indes). This article will focus on the points of convergence between the Old Indies and the Escalier des Ambassadeurs, or Ambassador’s Staircase, at Versailles – the decoration of which was being completed at the same time Johan Maurits presented his gift. Aimed at making tangible the possibility of colonial conquest, the immersive environments created by the tapestries and the staircase’s convincingly painted spectacle blurred the boundaries between reality and representation, mediating an ideological space that existed between the static, centralized authority of the French court and the far-flung colonial possessions it sought to acquire.